The southern diaspora : how the great migrations of Black and White Southerners transformed America - Gregory, James N. (James Noble) (University of North Carolina Press, 2005)
Weaving together the histories of black and white migrants, this book traces their paths and experiences, and demonstrates how this diaspora reshaped America by "southernizing" communities and transforming cultural and political institutions. It also shows how both black and white southerners used their new surroundings to become agents of change.